The clobazam metabolite N-desmethyl clobazam is an α2 preferring benzodiazepine with an improved therapeutic window for antihyperalgesia. (October 2016) - Ralvenius, William T.; Acuña, Mario A.; Benke, Dietmar; Matthey, Alain; Daali, Youssef; Rudolph, Uwe; Desmeules, Jules; Zeilhofer, Hanns Ulrich; Besson, Marie
Abstract: Data from genetically modified mice suggest that benzodiazepine (BDZ)-site agonists with improved selectivity for α2-subtype GABAA receptors (α2GABAA R) are potentially useful for the treatment of neuropathic pain. Subtype-selective compounds available for preclinical tests in rodents support this concept but have not been approved for human use, hindering proof-of-concept studies in patients. We recently proposed that N -desmethyl clobazam (NDMC), the main metabolite of the licensed BDZ clobazam (CBZ), is responsible for most of the antihyperalgesia observed in mice after CBZ administration. In order to assess a potentially favorable pharmacological profile of NDMC, we analyzed differences in the GABAA R subtype specificity of CBZ, NDMC and diazepam (DZP) in recombinant receptors. DZP and CBZ potentiated sedating α1GABAA Rs and antihyperalgesic α2GABAA Rs with similar efficacies, whereas NDMC preferred α2GABAA Rs over α1GABAA Rs across a wide concentration range. In vivo, DZP and NDMC reduced neuropathic pain at doses between 3 and 30 mg/kg. At these doses, DZP had strong locomotor sedating effects while NDMC caused no or only weak sedation. Sedative effects of NDMC became apparent when the action of NDMC was restricted to α1GABAA Rs. However, when GABAA R point-mutated mice were studied that allow the analysis of antihyperalgesia and sedation in isolation, we found that, compared to DZP, NDMC had a significantly improved therapeutic window, consistent with its more favorable α2/α1 in vitro activity ratio. Given that NDMC should share the safety profile of its parent compound CBZ, it should be well-suited for proof-of-concept studies in human volunteers or patients. Highlights: N -desmethyl clobazam is a naturally occurring metabolite of the approved clobazam. N -desmethyl clobazam possesses an improved α2/α1 GABAA R selectivity ratio. It exerts significant analgesia against neuropathic pain at non-sedative doses. N -desmethyl clobazam may be a well-suited for proof-of-concept studies in humans.